KAJIAN TIPOLOGI KUIL HINDU TAMIL PADA BANGUNAN GRAHA KATOLIK ANNAI VELANGKANNI DI MEDAN - Naibaho, Polin DR (Unika Santo Thomas, 2020)
The aim of this research is to identify the typology of Tamil Hindu temples were used on the architectural design of Graha Katolik Annai Velangkanni. As for the results of the research are Graha Katolik Annai Velangkanni adopted a form of Dravidian Tamil Hindu typology Style located in South India, with a pyramid-shaped tower with a shrink over the stair steps. It has seven levels of the building that symbolizes perfection and seven heavens, as well as three dome that symbolizes to Holy Trinity. One of the uniqueness in adopting the form of the Hindu Tamil Temple is in the zone of the altar (2nd floor), there is the opening up penetrate to the rear Tower as a place to enter the light from above so that the space feels more sacred altar with its natural lighting from the top of the tower. This typology is drawn from the concept of typology building Hindu temples namely space garbaha griha who continuously to the tower roof of vemana. The adoption of the other elements is taken from the form of animals (Peacock) and plants (Lotus, kalpataru and banana trees) where the ornaments found in the temples of Shrie Mariamman is a person (God), animals (elephants, birds) and plants (Lotus)